Tenascin C-Guided Nanosystem for Precision Delivery of Obeticholic Acid in Liver Fibrosis Therapy - Yawen Wang; Lei Yang; Qing Xu; Taiyu Liu; Hongliang He; Lisha Liu; Lifang Yin (Pharmaceutics)
Objective: Liver fibrosis, a hallmark of chronic liver diseases, is characterized by excessive extracellular matrix (ECM) deposition and scar tissue formation. Current antifibrotic nanomedicines face significant limitations, including poor penetration into fibrotic tissue, rapid clearance, and suboptimal therapeutic efficacy. The dense fibrotic ECM acts as a major physiological barrier, necessitating the development of a targeted delivery strategy to achieve effective therapeutic outcomes. Methods: We designed a liposomal delivery system functionalized with the GBI-10 aptamer and encapsulating obeticholic acid (OCA lips@Apt) to enhance selective delivery to fibrotic liver tissue while minimizing systemic toxicity. Results: Both in vitro and in vivo studies demonstrated that the aptamer-modified OCA liposomes effectively treated hepatic fibrosis through dual mechanisms: modulation of abnormal bile acid metabolism and attenuation of inflammation. The targeted delivery system leveraged the overexpression of Tenascin-C (TnC), a key ECM component in fibrotic tissues, for precise localization and enhanced endocytosis via the exposed cationic liposome surface. Conclusions: The OCA lips@Apt nanodrug demonstrated superior therapeutic efficacy with minimal off-target effects, offering a promising strategy to overcome critical barriers in liver fibrosis treatment. By precisely targeting the fibrotic ECM and modulating key pathological pathways, this TnC-guided liposomal delivery system provides a significant advancement in antifibrotic nanomedicine.